Nutrition Education During Pregnancy Increases Pregnant Women's Knowledge in Preventing Stunting - Nadya Fitriani; Nur Indah Nasution; Nurhayani Harahap (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Stunting is a result of chronic malnutrition experienced by a person during pregnancy and early birth, which can increase infant and child mortality, make them susceptible to illness, and inhibit growth and development. The aim of the activity is to provide education about pregnancy nutrition to prevent stunting. The targets were 10 pregnant women in Tanjung Anom Village. The service methods are counseling and discussion. The results of the activity showed that after being given education, there was an increase in pregnant women's knowledge about nutrition during pregnancy and efforts to prevent stunting. Advice to village midwives and local Posyandu cadres to provide assistance to pregnant women in meeting nutritional needs in order to prevent stunting in future children.